Peran Institusi Akademik dalam Menangkal Ideologi Ekstrem dalam Membangun Ketahanan Nasional melalui Pendidikan - Ragil Ira Mayasari (Journal on Education, 2025)
Radicalism is a complex phenomenon that can appear in various forms, both in the context of religion, politics, and other ideologies. In the context of education, radicalism is of particular concern because the academic environment can be a means for the spread of extreme ideologies and their prevention. This study aims to analyze the relationship between education and radicalization and explore how the curriculum and academic environment influence a person's tendency towards extreme ideologies. Using qualitative methods through a case study approach and systematic literature review, this study found that an educational curriculum that emphasizes critical thinking, values ​​of tolerance, and multicultural insight can prevent radicalization. Conversely, an education system that is rigid, dogmatic, and provides little space for discussion can be a trigger for the development of radical ideologies. The academic environment also plays an important role in shaping students' mindsets, where the influence of lecturers, social groups, and access to information can determine the tendency towards extreme ideologies. Therefore, educational institutions need to adopt more inclusive policies, support diversity, and strengthen digital literacy and citizenship in order to counter radicalization among academics.